Screening of different species reveals cat hepatocytes support HBV infection. - Zaichao Xu; Kaitao Zhao; Jingjing Wang; Lu Zhang; Jiatong Yin; Nijing Chen; Sijia Chen; Gaihong Zhao; Mengfei Wang; Tailai Xin; Chengliang Zhu; Xiaoming Cheng; et al. (PLoS Pathogens)
Hepatitis B virus (HBV) remains a major public health challenge, with nearly 300 million chronic infections, yet research is hindered by the lack of suitable animal models. This study aimed to identify HBV-susceptible species and establish a novel infection model. Primary hepatocytes from humans, cats, rabbits, Syrian hamsters, Siberian hamsters, guinea pigs, bulls, goats, pigs, cynomolgus macaques, and dogs were assessed for HBV entry using hepatitis D virus (HDV) infection. HBV relaxed circular DNA (rcDNA) transfection was performed to evaluate its repair into covalently closed circular DNA (cccDNA). HBV infection assays were conducted in vitro. Results showed that primary hepatocytes from humans and cats were susceptible to HDV, suggesting their potential to support HBV entry. All tested hepatocytes converted rcDNA into cccDNA, confirming their ability to complete early HBV replication steps. Notably, cat hepatocytes uniquely supported HBV infection, displaying time-dependent viral replication marker expression. Cat hepatocytes also responded to antiviral treatments, underscoring their relevance for drug evaluation. This study provides the first evidence that cats can support HBV infection in vitro, offering a promising new platform for HBV research and antiviral development.